A Multicenter Survey of Type I Diabetes Mellitus in Chinese Children - Hou, Ling; Li, Xiuzhen; Liu, Li; Wei, Hanyang; Xiong, Feng; Du, Hongwei; Yang, Yu; Zhang, Huifeng; Zhang, Qin; Yao, Hui; Fu, Junfen; Yan, Xiaoli; et al. (Frontiers in Endocrinology, 2021)
Purpose To investigate the features and treatment status of children with type 1 diabetes mellitus (T1DM) in China. Methods We recruited patients <14 years of age with T1DM from 33 medical centers in 25 major cities of China between January 2012 and March 2015. All patients completed a questionnaire that was conducted by their pediatric endocrinologists at all centers. Results A total of 1,603 children (755 males and 848 females) with T1DM participated in this survey. Of these, 834 (52.03%) of the patients exhibited diabetic ketoacidosis (DKA) at onset, while 769 patients (47.97%) did not exhibit DKA (non-DKA) at onset. There was a higher proportion of females (55.71%) in the cohort of patients exhibiting DKA at onset than in the non-DKA cohort (49.33%). The mean age of patients exhibiting DKA at presentation was 7.12 ± 0.14 years; this was significantly younger than that in non-DKA group (7.79 ± 0.15 years; P < 0.005). The frequency of DKA in 3 years old, 3-7 years old, and 7 years old or more was 77.21%, 26.17%, and 37.62%, respectively. Upon initial diagnosis, 29.4%, 15.2% and 11.8% of patients showed positivity for glutamic acid decarboxylase antibody (GADA), Insulin autoantibodies (IAA), or islet cell antibody (ICA), respectively. During six months follow-up, 244 patients (15.21%) reported receiving insulin pump therapy, and more than 60% of patients monitored their blood glucose levels less than 35 times per week. Although the majority of patients had no problems with obtaining insulin, 4.74% of the children surveyed were not able to receive insulin due to financial reasons, a shortage of insulin preparations, or the failure of the parents or guardians to acquire the appropriate medicine. Conclusion DKA is more common in very young children. Treatment and follow-up of T1DM in China still face very serious challenges.